Glucose Overload Inhibits Glutamatergic Synaptic Transmission: A Novel Role for CREB-Mediated Regulation of Synaptotagmins 2 and 4 - Ripoli, Cristian; Spinelli, Matteo; Natale, Francesca; Fusco, Salvatore; Grassi, Claudio (Frontiers in Cell and Developmental Biology, 2020)
Glucose metabolism derangement is critically involved in the age-related memory loss but the underlying molecular mechanisms are still poorly understood. In a mouse model of type 1 diabetes we found memory impairment associated with inhibition of the transcription factor CREB and alteration of pre- and post-synaptic protein expression in the hippocampus. Accordingly, glucose excess negatively affected activity-dependent CREB phosphorylation and CREB-mediated mRNA expression of synaptic proteins in hippocampal primary neurons. Specifically, glucose excess inhibited the activity-dependent recruitment of CREB on the regulatory sequences of synaptotagmin (SYT) 2 and 4 promoters and the expression of SYT4 protein. As a result, high glucose affected both the frequency of miniature excitatory post-synaptic currents and NMDA receptor-mediated currents in autaptic hippocampal neuronal cultures. Collectively, our findings highlight novel mechanisms underlying hyperglycaemia-related memory loss, including CREB-dependent downregulation of synaptotagmin expression.